Glossal cysts in four infants. Issue 11 (November 1987) - Harari, M D; Clezy, J K; Sharp, E
Abstract : Cysts at the base of the tongue causing stridor may be fatal if they are not recognised and treated. Digital palpation along the surface of the tongue to the epiglottis is a useful diagnostic method. An operative technique that might avoid the need for tracheostomy is described.